Pemberdayaan Ekonomi Lokal dengan Inovasi Minuman Sehat Berbahan Kedelai melalui Wirausaha di Desa Kasri, Kecamatan Bululawang - Dura, Justita; Cahyaningtyas, Fadilla; Hanif , Rifki; Hadi, Abd; Rofiq, Mohammad (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
SMEs are one of the important pillars of the Indonesian economy which also has an impact on current conditions. The main problem faced by SMEs is that they are very lacking in digging for information about the development of THEIR SMEs because the people in Kasri Village who are still thinking about their main livelihood, namely farming, there are actually business opportunities in this village. The purpose of this activity is so that people can improve the mindset of entrepreneurs, develop businesses for existing ones, and create product innovations so that they are not monotonous so that their lives are more advanced and developed. And the community can create superior products so that they can advance the local village economy. Therefore, this community service activity is to help the community to improve soy products such as processed soy milk, improve the quality and quantity of soy products by providing alternative product variations such as tempeh chips with flavor variants, expand marketing networks, and provide simple financial recording training